Targeting endoplasmic reticulum stress-induced CLGN resensitizes hepatocellular carcinoma to apoptosis: paeonol synergistically enhances efficacy by dual inhibition of CLGN and NF-κB - Yan, Sitong; Wang, Anqi; Chen, Xiang; Jiang, Weijia; Du, Xiao; Huang, Yuhan; Zu, Xiangyu; Zhu, Yue; Liu, Jiatao; Fan, Lulu; Zhang, Lingling; Sun, Guoping (Frontiers in Oncology, 2025)
PurposeEndoplasmic reticulum stress (ERS) drives hepatocellular carcinoma (HCC) progression and therapy resistance. This study identifies Calmegin (CLGN) as a novel ERS-induced pro-survival factor and explores shCLGN combined with Paeonol (Pae) to overcome apoptosis resistance via NF-κB suppression.Materials and methodsCLGN was discovered by transcriptome sequencing of tunicamycin (TM)-induced ERS in HepG2 cells and validated via Western blot. Clinical significance was assessed using 93 paired HCC/adjacent tissues (IHC/WB) and TCGA data. Functional roles of CLGN (proliferation: CCK-8/EdU; migration/invasion: Transwell; apoptosis: flow cytometry). shCLGN efficacy alone or with Pae was tested in vitro and in vivo (xenografts). Transcriptome sequencing combined with Western blot was performed after sh-CLGN to confirm that CLGN regulates apoptosis-related proteins (such as Bcl-2, Bax, and Caspase-3) through the NF-κB pathway, as well as the mechanism of sh-CLGN combined with paeonol on the pathway.ResultsERS significantly upregulated CLGN in HCC, correlating with advanced tumor stage and poor prognosis. CLGN promoted proliferation/migration and suppressed apoptosis. Crucially, sh-CLGN sensitized HCC cells to Pae, synergistically enhancing apoptosis and tumor suppression. Mechanistically, CLGN sustained survival via NF-κB activation; the combination (sh-CLGN + Pae) dual-blocked CLGN/NF-κB, reversing pro-survival signaling in vitro and in vivo.ConclusionCLGN is a pivotal ERS effector mediating HCC apoptosis resistance through NF-κB. Sh-CLGN combined with Pae restores apoptotic sensitivity via dual CLGN/NF-κB inhibition, providing a potent strategy against ERS-adapted HCC.